PREMARITAL HEALTH EDUCATION THROUGH EDUCATIONAL MEDIA ON IMPROVONGING THE HEALTH KNOWLEDGE OF PROSPECTIVE BRIDES AND GROOMS - Febriyona Lathifah; Gina Muthia; Putri Nelly Syofiah; Ririn Yesma Anwar; Dina Islamika Fitrah (PT. Jurnal Center Indonesia Publisher, 2025)
The objective of this research was to prove whether using Choral Reading strategy can improve reading comprehension of the eight grade students of SMP Negeri 13 Palu. This research limited the use of Choral Reading strategy in improving students' reading comprehension, which focuses on literal meaning and descriptive text. This research used quasi-experimental research design involving an experimental class and a control class. The sample of this research were students of VII B as the experimental class, which consisted of 31 students, and the students of VIII A as the control class, which consisted of 31 students. The data was collected through pre-test and post-test. The results confirmed that the mean score of the experimental class had increased from 44.87 to 73.83. On the other hand, in the control class, it has increased from 48.29 to 62.64. The results of the test were analyzed statistically by applying 0.05 level of significance. The researcher found that the value of the t-count was higher than the t-table (4.59 > 1.67). In other words, the implementation of choral reading strategy can develop students' reading comprehension of the eighth-grade students of SMP Negeri 13 Palu. This strategy has a significant impact on the English learning process, especially helping students in reading comprehension to find information about the text and understand the entire meaning of the text, so that students can practice choral reading as their independent reading comprehension strategy in the future